1995
DOI: 10.1128/jb.177.21.6033-6040.1995
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two genes encoding proteases associated with the mycelium of Streptomyces lividans 66

Abstract: A strain of Streptomyces lividans 66 deleted for a major tripeptidyl aminopeptidase (Tap) was used as a host to screen an S. lividans genomic library for clones overexpressing activity against the chromogenic substrate Ala-Pro-Ala-␤-naphthylamide. In addition to reisolation of the tap gene, clones representing another locus, slpD, were uncovered. slpD was analyzed by deletion subcloning to localize its functional sequence. Nucleotide sequence determination revealed an open reading frame encoding a 55-kDa prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…Rv2224c is classified as an ␣/␤ hydrolase in a family with both esterase and amidase members (25). Its closest biochemically characterized homolog, the secreted SlpD triaminopeptidase from S. lividans, was identified by its activity against an amide (7). Protease activity is consistent with the requirement of Rv2224c for correct processing of GroEL2.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Rv2224c is classified as an ␣/␤ hydrolase in a family with both esterase and amidase members (25). Its closest biochemically characterized homolog, the secreted SlpD triaminopeptidase from S. lividans, was identified by its activity against an amide (7). Protease activity is consistent with the requirement of Rv2224c for correct processing of GroEL2.…”
Section: Discussionmentioning
confidence: 73%
“…Rv2224c contains a GXSXG consensus sequence surrounding a putative serine active site (S 228 ), which is characteristic of ␣/␤ hydrolase-fold family members, namely proteases, esterases, and lipases. Rv2224c is annotated as a tripeptidyl peptidase in the MEROPS peptidase database, and its sequence shows high sequence similarity to the serine proteases SlpD and SlpE from Streptomyces lividans, which are mycelium-associated lipoproteins involved in cell growth (7). Refolded recombinant Rv2224c also has been reported to display esterase activity in vitro (8).…”
Section: Rv2224c Is Associated With the Mycobacterial Cell Envelopementioning
confidence: 99%
“…This observation highlighted the difference in function(s) of the prx gene product and the S. lividans SlpE protease that is required for the effective growth of the strain on minimal media (Binnie et al, 1995). The mutant thus obtained grew and sporulated well on both complete and minimal media.…”
Section: Disruption Of Prx Affected Lae Production In Streptomyces Glmentioning
confidence: 84%
“…A 1 kb upstream section of lndI short non-overlapping DNA fragments had been found that showed homology to bacterial proteinases. Putative proteinases found in the Streptomyces coelicolor (genes SCO5180, SCO4241, SCO3540, SCO5179) and Streptomyces avermitillis (SAV3081, SAV3080) genomes (Bentley et al, 2002;Ikeda et al, 2003), as well as the previously studied Streptomyces lividans proteases SlpD and SlpE (Binnie et al, 1995) are the closest Prx homologues, with a similarity ranging from 55% to 72%. It was situated 700 bp upstream of lndI and had the same transcriptional direction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It could even act on highly stable secreted proteins since depletion of this protease increased yield of extracellular a-amylase . In S. lividans, Binnie et al (1995) described two cell-associated proteinases, SlpD and SlpE. It is suggested that the function of these cell-associated proteases resembles that of E. coli DegP protease.…”
Section: )mentioning
confidence: 99%